2000
DOI: 10.1002/(sici)1099-1085(20000228)14:3<557::aid-hyp954>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behaviours of anoxic saline water in Lake Abashiri, Hokkaido, Japan

Abstract: Lake Abashiri (surface area 32 . 87 km 2 ; maximum depth 16 . 2±16 . 5 m) is consistently strati®ed by the lower anoxic saline layer (salinity 14±20%; dissolved oxygen less than 0 . 1% Sat.). Behaviours of the lower saline water are investigated by continuously and vertically measuring¯ow velocity, salinity and water temperature, and by observing meteorology, river discharge, lake level, sea level and water properties. During the period of ow measurement (June±August 1997), the sea level remained higher than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…If no layer of equal density is encountered, the underflow can continue into the deep hypolimnion. This conceptual model is at the basis of numerous models (Akiyama & Stefan, 1984;Ellison and Turner, 1959;Hebbert et al, 1979;Parker et al, 1986;Savage and Brimberg, 1975) and has qualitatively been confirmed by observations in lakes and reservoirs (Chikita, 2000;Fischer and Smith, 1983;Fleenor, 2001;Ford and Johnson, 1983;Giovanoli and Lambert, 1985;Hebbert et al, 1979;Lambert and Giovanoli, 1988;Piton et al, 2022;Soulignac et al, 2021).…”
Section: Introductionsupporting
confidence: 70%
“…If no layer of equal density is encountered, the underflow can continue into the deep hypolimnion. This conceptual model is at the basis of numerous models (Akiyama & Stefan, 1984;Ellison and Turner, 1959;Hebbert et al, 1979;Parker et al, 1986;Savage and Brimberg, 1975) and has qualitatively been confirmed by observations in lakes and reservoirs (Chikita, 2000;Fischer and Smith, 1983;Fleenor, 2001;Ford and Johnson, 1983;Giovanoli and Lambert, 1985;Hebbert et al, 1979;Lambert and Giovanoli, 1988;Piton et al, 2022;Soulignac et al, 2021).…”
Section: Introductionsupporting
confidence: 70%
“…These situations typically correspond to days with high temperatures and irradiance. In some systems, anoxia near the surface can result from the upwelling of poorly oxygenated deep waters due to wind influence (Chikita, 2000;Sanford et al, 1990).…”
Section: Locationmentioning
confidence: 99%
“…In particular, the shallower depth where the oxycline now intersects the basin slope around the perimeter of the inner basin will essentially translate to a reduction in the extent of viable habitat for aerobic organisms. In Furnace (Kelly et al 2018 b ) and similar deoxygenated estuaries (e.g., Sanford et al 1990; Chikita 2000), baroclinic waves can dramatically influence dissolved oxygen conditions in nearshore areas. A shallower oxycline following ventilation will therefore mean that upwelling anoxic water could encroach further on communities of nearshore benthic organisms.…”
Section: Discussionmentioning
confidence: 99%